Porosity prediction through hydrogen bonding in covalent organic frameworks - Karak, Suvendu; Kumar, Sushil; Pachfule, Pradip; Banerjee, Rahul (Journal of the American Chemical Society, 2018)
Easy and bulk-scale syntheses of two-dimensional (2D) covalent organic frameworks (COFs) represent an enduring challenge in material science. Concomitantly, the most critical aspect is to precisely control the porosity and crystallinity of these robust structures. Disparate complementary approaches such as solvothermal synthesis have emerged recently and are fueled in part by the usage of different modulators and acids that have enriched the COF library. Yet, the fundamental understanding of the integral processes of 2D COF assembly, induding their growth from nucleating sites and the origin of periodicity, is an intriguing chemical question that needs to be answered. To address these cardinal questions, a green and easy-to-perform approach of COF formation has been delineated involving acid-diamine salt precursors. The role of hydrogen bonding [d(av)(N-amine-H center dot center dot center dot O-acid); d(av) signifies the average N-amine-H center dot center dot center dot O-acid distances, i.e., the average distance from the H atom of the amine to the O atom of the acid] present in the acid-diamine salts in improving the COFs' crystallinity and porosity has further been decoded by thorough crystallographic analyses of the salt molecules. What is particularly noteworthy is that we have established the hydrogen-bonding distances d(av)(N-amine-H center dot center dot center dot O-acid) in the acid-diamine salts that are pivotal in maintaining the reversibility of the reaction, which mainly facilitates highly crystalline and porous COF formation. Moreover, this reactant-structure to the product-quality relationship has further been utilized for the synthesis of highly crystalline and porous COFs that are unattainable by other synthetic means.